Psychometric properties and measurement methods of the Adult Attention and Hyperactivity Disorder Self-Report Scale Screener (ASRS-Screener) in the population of Lima. - Robles, Yolanda I. (2021)
Objectives: To determine the distribution of scores, reliability, validity and association with sociodemographic variables of the Self-Report Scale of Attention Deficit Hyperactivity Disorder in adults - Screening (ASRS- Screening) in the population of Lima and Callao, according to two rating scales (binary and Likert), and to establish the concordance between both of them. Material and Methods: Study based on data from the Epidemiological Mental Health Study of Metropolitan Lima 2012 - Replication, in a sample of 4 445 people, 18 years or older (42.6 ± 17.4). Results: The average of the ASRS-Likert screening was 3.74 + 3.9 (range 0-21), internal consistency using Cronbach alpha coefficient = 0.806, McDonald’s omega coefficient = 0,869, and factor analysis showed 52.95% of the total inertia explained by a single factor. In binary scale. mean = 0.89 + 1.27 (range 0-6), Cronbach alpha = 0.599, McDonald’s omega=0,753, and 52.31% of the inertia was explained by two factors. With both scales, Kappa coefficient showed 0.734 of concordance of positive screenings. The two forms of qualification are associated with age whereas only binary classification was with marital status and educational level. Conclusions: ASRS-Screening is an instrument of acceptable internal consistency. Its factorial structure and the prevalence of positive screenings vary in accordance with the Likert or binary measurement form.